Organizational Communication for Excellent Education: A Model at Modern Islamic Elementary School Raudhatul Ma’arif, Bungo - Handoko, Yudo (Journal of Education Method and Learning Strategy, 2024)
This study aims to explore and discover the model of organizational communication effectiveness on learning in MI Modern Raudhatul Ma’arif, Muara Bungo, Jambi. Effective communication among teachers, school staff, and students plays a crucial role in formulating clear learning objectives and facilitating a better understanding of academic expectations. Communication enhances teaching quality by supporting open exchanges of knowledge and experiences. The involvement of parents is considered crucial, and strong organizational communication can strengthen collaboration between the school and families. Limited organizational communication can lead to misunderstandings, job dissatisfaction, and obstacles to achieving optimal educational outcomes. A qualitative method with the Grounded Theory approach was employed, involving various stakeholders such as teachers, students, parents, and administrative staff. This research is essential in understanding how organizational communication influences learning, teaching quality, and parental involvement in the continuously evolving education landscape. The study findings indicate that MI Modern Raudhatul Ma’arif has successfully established harmony between formal and informal communication, making organizational communication a cornerstone in achieving school objectives. The holistic and effective organizational communication model in MI Modern Raudhatul Ma’arif can serve as an example for other schools, providing a foundation for an inclusive, transparent, and positive educational atmosphere.